Trauma as a borderland concept in contemporary South African painting - Webster, Jessica (My University, 2010)
Abstract In this report I explore trauma as a concept in contemporary painting. I interpret certain South African paintings that assert the affective dimension of the painted surface as particularly compelling manifestations of a concept of trauma. I frame my discussion in terms of Mark Seltzer’s (1997:5) theory of trauma as a ‘borderland concept’. I see Seltzer’s concept as analogous to certain formal values these South African paintings deploy in relation to the painted surface, primarily the tension between materiality and iconography, form and formlessness, figure and ground and surface and depth. I draw on aspects of psychoanalytic theory and discourses on contemporary painting to support my discussion. I analyze selected paintings by Marlene Dumas and Penny Siopis within this framework. I also discuss my own paintings and Masters exhibition as pertaining to a concept of trauma. I argue that trauma as a borderland concept offers a means of appraising contemporary painting in a way that resists an overly semantic or purely perceptual interpretation.